CONCEPTUALIZING THE INFLUENCE OF ENVIRONMENTAL KNOWLEDGE ON PERCEIVED VISIT VALUE TO GREEN RESORT IN MALAYSIA - Nor Rabiatul Adawiyah Nor Azam; Basri Rashid; Noor Azimin Zainol, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Globally, going- green is a growing trend within the hotel industry. The past several decades have seen a growing awareness amongst hoteliers and investors regarding the environmental and social impacts of hotel development and operations. This conceptual paper aims to investigate the influence of environmental knowledge and perceived value on a visit to a green resort. At present, inadequate information related to environmental knowledge among guests who are considering to make a visit to a green resort has become the main impediment to both local and international marketers in developing a successful business and marketing strategies about green products or services. Thus, it is imperative to understand guests’ perceived values about green resorts, especially in Malaysia. Applying desk analysis through an indepth reviews of literatures, this paper suggest there is theoretical evidence that suggest the relationship between customer environmental knowledge and their perceived values namely functional value, social value, epistemic value and emotional value. The findings of this study will provide an insight into the practices of green resort practitioners. It is feasible for green resort practitioners to promote of environmental activities to encourage the use of environmentaly products and services, encouragement of the involvement of green resort guest in reuse, recycling and thus helping to preserve the environment.